A rare case of cutaneous involvement in atypical haemolytic uraemic syndrome successfully treated with eculizumab - Lopes,Daniela (2016)
Atypical haemolytic uraemic syndrome (aHUS) is a rare, life-threatening, genetic disease, due to uncontrolled alternative pathway complement activation. Although the renal microvasculature appears to be the predominantly affected target, other organ pathology compatible with local thrombotic microangiopathy has been reported. Eculizumab is a humanized antibody therapy that has been associated with significant inhibition of complement-mediated thrombotic microangiopathy events in aHUS. In this report, we describe the rare case of a patient with relapsing atypical haemolytic uraemic syndrome, cutaneous manifestations of the thrombotic microangiopathy and we discuss the treatment with plasma exchange and eculizumab